Biplane Medial Opening-Wedge High Tibial Osteotomy Increases Posterior Tibial Slope more than Uniplane Osteotomy - Suh, Dong Won; Nha, Kyung Wook; Han, Seung Beom; Cheong, Kuhoang; Kyung, Bong Soo (The Journal of Knee Surgery, 2021)
Few clinical studies have compared uniplane high tibial osteotomy (HTO) with biplane HTO. The study aim was to compare the radiological and clinical results of uniplane HTO and biplane HTO, especially in terms of the increase in the posterior tibial slope (PTS). Medial opening-wedge HTO patients' medical records and radiological results from a single institution were retrospectively reviewed. Pre- and postoperative serial radiographs, including the Rosenberg, lateral view, and standing anteroposterior view of the whole lower extremity, magnetic resonance imaging at postoperative day 2, and the Western Ontario and McMaster Universities Arthritis Index (WOMAC) score at postoperative 2 years were reviewed to evaluate radiological and clinical results, including the change in PTS. A total of 61 knees, including 34 for uniplane and 27 for biplane HTOs, were enrolled. There were no significant differences in the pre- and postoperative mechanical angles or incidences of the lateral hinge fractures, and all patients showed complete union at postoperative 2 years. The PTS was increased more in the biplane group than in the uniplane group (3.1 ± 2.6 in biplane vs. 0.8 ± 1.7 in uniplane, p < 0.05). The WOMAC scores were 72 ± 9.3 in the uniplane and 75 ± 5.8 in the biplane group (not significant). The increase in PTS was lower in uniplane medial opening HTO than in biplane HTO.
Keywords: medial compartment osteoarthritis; high tibial osteotomy; uniplane osteotomy; biplane osteotomy; posterior tibial slope